145k views
4 votes
Solve for the variable.

3(2x-4)+6=30

x=___

User Aryn
by
4.9k points

2 Answers

5 votes

Answer:

x = 6

Explanation:

Simplify 3(2x-4) first: 3 (2x) 3(-4) =

6x - 12+6 = 30

Combine like terms: -12 + 6 = -6

6x - 6 = 30

Add 6 to both sides: 6x = 36

Divide both sides by 6: x = 6

CHECK:

3( 2(6) - 4) +6 = 30

3 (12-4) +6 = 30

3(8) +6 = 30

24+ 6 = 30

30 = 30

User Alki
by
5.2k points
5 votes

Answer:

x = 6

Explanation:

Use distributive property: a(b + c) = a*b + a*c

3(2x - 4) + 6= 30

3*2x - 3*4 + 6 = 30

6x - 12 + 6 = 30

6x - 6 = 30

6x = 30+ 6

6x = 36

x = 36/6

x = 6

User Kobbe
by
5.1k points